Effects of functional antioxidants on the expansion of gamma delta T-cells and their cellular cytotoxicity against bladder cancer cells - Yueh Pan; Hung-Jen Shih; Shu-Han Chuang; Chin-Pao Chang; Chi-Hao Hsiao; Ya-Hsu Chiu; Pai-Fu Wang; Chi-Chen Lin; Ping-Hsiao Shih (BMC Cancer)
Abstract Purpose Results of previous studies have demonstrated that T-cell receptor cross-linking rapidly generates reactive oxygen species, which play essential signaling roles within mitochondria for the antigen-specific expansion of T-cells. However, oxidative stress also causes damage to cellular organelles. Thus, modulating ROS metabolism using antioxidants during naïve T-cell activation may promote the expansion and generation of functional T-cells. Notably, urothelial cancer is a sex-specific malignancy with high mortality rates worldwide. The present study aimed to evaluate the effects of various antioxidants on γδ T-cell proliferation, and the associated cytotoxicity against urothelial carcinoma cells (UCs). Methods Over a period of cell induction and expansion, peripheral blood mononuclear cells were cultured with or without different antioxidants, including N-acetyl cysteine (NAC), vitamin C and vitamin E. Subsequently, phenotypic characterization of γδ T-cells and their cytolytic effects against UCs were analyzed by flow cytometry and cell viability assays, respectively. Results and Conclusions The results revealed that NAC partially inhibited T-cell expansion in a dose-dependent manner. In addition, CD3+/Vγ9+ levels and natural killer group 2D receptor expression were mildly reduced following treatment with a high dose of NAC, whereas CD3+/CD56+ levels and CD314 expression in natural killer-like cells were moderately decreased following treatment with vitamin E. Particularly, the direct co-incubation of bladder cancer cells with γδ T-cells supplemented with antioxidants significantly enhanced bladder cancer cytolysis. Collectively, results of the present study revealed that co-administration of functional antioxidants during γδ T-cell expansion may enhance the quality and efficacy of adoptive T-cell therapies for cancer treatment.